SYNTHESIS OF AMYLOSE AND AMYLOPECTIN BRUSHES ON SILICON WAFER SURFACE - MANDIRI VIDYAWARDHANI (NIM: 20507020), PRADANTI
Polysaccharides are polymer from nature that have attracted new interest as advanced materials due to its biocompatibility, structure-forming capacity, and environmentally friendly property. One of its application field is to synthesis polymer brushes from amylose and amylopectin. This type of polymer can be synthesized via enzymatic polymerization by using phosphorylase and glycogen branching enzyme. Silicon wafers were used as solid support and polymers were grown from it. Polymer brushes can be obtained after three steps of reaction: modifying the surface of silicon wafers with (3-aminopropyl)trimethoxysilane (APTMS), grafting maltoheptaose as a primer to silicon surface, and enzymatic polymerization of the primer. To understand polymers property on silicon wafer surface especially layer thickness and roughness, three different glucose-1-phosphate (G1P) concentrations have been used. Characterizations were done by using infra red (IR), x-ray photoelectron spectroscopy (XPS), and atomic force microscopic (AFM). The kinetics and surface density of the amine group was also calculated. According to IR spectrum, amylose and amylopectin brushes have been successfully synthesized but can not be disthinguished. XPS data were also give the same results. The roughness of the layer on the surface was determined by using AFM but it still can not be concluded whether the concentration of G1P has an effect towards it. The thickness of the layer on the surface has been calculated but can only be applied to amylose brushes. Kinetic measurement showed that amylopectin wafers always grow faster than amylose wafers for every G1P concentration used in this research. Determination of surface density of the amine group concludes that the amount of APTMS has been attached to silicon wafer was 1.86 molecule/nm2 meanwhile for maltoheptaose, it gives value of 0.45 molecule/nm2.